THE LATEST TECHNOLOGY PARADIGM IN EDUCATION: THE ROLE AND CONTRIBUTION OF GAME-BASED LEARNING (GAMIFICATION) IN INCREASING STUDENT MOTIVATION - Andy Rachman; Buntara Adi Purwanto; Tri Kurniah Lestari (International Journal of Teaching and Learning, 2025)
One of the newest technological trends in education is game-based learning, or gamification. The use of game design features and principles in non-gaming situations, such education, to boost user motivation, engagement, and involvement is known as gamification. Gamification is a significant factor in making learning more engaging and fun for students in the setting of education. Gamification holds enormous promise for boosting student enthusiasm and involvement in the classroom. Gamification can be a useful tool in helping students have more meaningful and engaging learning experiences provided it is designed and implemented well. Student motivation and achievement can be significantly enhanced by the use of game-based learning. By creating interactive, immersive, and enjoyable learning experiences, this approach can stimulate student interest and improve the quality of their understanding of the subject matter. However, it should be remembered that the success of game-based learning lies in careful design, proper integration into the curriculum, and careful monitoring of student responses to ensure success in achieving learning objectives.